2x-12=-26

Simple and best practice solution for 2x-12=-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-12=-26 equation:


Simplifying
2x + -12 = -26

Reorder the terms:
-12 + 2x = -26

Solving
-12 + 2x = -26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 2x = -26 + 12

Combine like terms: -12 + 12 = 0
0 + 2x = -26 + 12
2x = -26 + 12

Combine like terms: -26 + 12 = -14
2x = -14

Divide each side by '2'.
x = -7

Simplifying
x = -7

See similar equations:

| -5(p-2)+3p=6(p-4) | | R^2+16r-76=0 | | 6x2-12x-48/3x2-12x-36 | | 11p^2=-1 | | 4(7x-10)=18 | | x^5-6x^2+3x+3=0 | | y^2-3ay+2a^2=0 | | g(2)=4t^2-5t+3 | | (12a^3bc-^4/-4ab^5c^2)^3 | | -24x+4y=12 | | 14p^2-59p+35=0 | | g(t-2)=4t^2-5t+3 | | 2.5x-25=12 | | 2.5x-15=12 | | 5a-11=8a+8+14a+1 | | 4x(5*3x)=0 | | -16t^2+25t+5=0 | | 5x-7=-2(3-8+1) | | Z=8-y | | 1/13+1/4-1/52= | | 28/44= | | 4x=2(x-3)-8 | | g(t)-g(2)=4t^2-5t+3 | | 12(3y+x)= | | 2=-1/5x | | 0=4x^2-405x+40380 | | 9/2×90 | | 15n^2+13n-20=0 | | 19300/30000x100 | | 20=d+(-5) | | 3(x-2)(x-2)=36 | | 3(x^2+4)-36=0 |

Equations solver categories